Ali vadba z žogo bosu vpliva na dinamicno in staticno ravnotežje pri mladostnikih taekwondoistih - Ipekoglu, G.; Karabiyik, H.; Er, F.; Suveren Erdogan, C.; Cakir, E.; Koz, M.; Baltaci, G.; Colakoglu, F. F. (Kinesiologia Slovenica, 2018)
The purposes of this study were to develop taekwondo-specific core stabilization-balance training and to determine the influence of a core stabilization-exercise protocol, using the BOSU, on dynamic and static balance performance in adolescent TKD athletes. Twenty-four elite taekwondo athletes were randomly divided into two groups: the BOSU-trained group (n = 13) and the control group (n = 11). Subjects in BOSU-trained group had core-stabilization training 3 times a week for 12 weeks in addition to the routine taekwondo training program. The control group had no training protocol in addition to the routine taekwondo training program. Static and dynamic balances of the subjects, both right and left legs were assessed with the Biodex Balance System. ANOVAs showed that the BOSU decreased both the static and the dynamic balance error scores of non-dominant leg from pre to post-training by 0.32±0.17 (28.5%) and 0.75±0.47 (82.5%); respectively (p<0.05). Furthermore, the BOSU decreased the dynamic balance error scores of dominant leg from pre to post-training by 40.33% (p<0.05). This study demonstrates that the taekwondo-specific BOSU training program is effective in decreasing the balance error scores in dominant and non-dominant leg. It is suggested that the BOSU training can be applied as an effective exercise program for enhancing dynamic and static balance performance.